(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The referendums on the modification of art. 41 of the Irish Constitution ABSTRACT: The aim of this essay is to describe and briefly analyse the events that lead to the referendum aiming to modify art. 41 of the Irish Constitution, and the position adopted by some important denominations towards the vote. SOMMARIO: 1. Introduzione - 2. Gli antecedenti - 3. La Citizens’ Assembly on Gender Equality - 4. Verso il referendum - 5. Il testo dei referendum - 6. Le confessioni religiose e i referendum - 7. Il voto - 8. Alcune brevi considerazioni.